Malaysia Constitutional Law System, Study On The Use Advanced Searching Algorithm (Rule-Based And Horspool Algorithm) - Abd Razak, Nuur Farhani (2017)
Page quality are important to make a good application. Many researchers are implements the page quality using the advanced searching algorithm. To make a good of the average page quality of the Malaysia statute federal constitutional are important for success this study. The federal constitutional has a lot of interrelated acts for every page. Therefore, it is difficult for the users to find all the inter-related acts from the federal constitutional using manual method. In this research, we study about the concept of advanced searching algorithm to build an intelligent web based system. We hope after build the intelligent web based system can solved the problem that user's faced.